A perspective on food addiction through gut microbiota - Erkul, Cahit (Journal of Dependence, 2024)
Eating behavior is characterized by the balance between homeostatic and hedonic regulatory mechanisms and is highly influenced by environmental signals. Eating behavior depends on internal and external factors such as genetics, taste of food, and environment. The gut microbiota is an important environmental contributor to host physiology and influences feeding behavior. Additionally, the gut microbiota performs numerous functions in the body: Appetite and satiety control, production of neurotransmitters and other metabolites. Although there is still an ongoing debate about the concept of food addiction, studies agree that patients with food addiction behavior exhibit symptoms similar to those experienced by drug addicts, affecting central areas involved in the control of motivated behavior. Little work has been done to answer how the microbiota may influence behaviors associated with “food addiction.” Although research to date has not yet been completed, a growing body of evidence demonstrates how microbiota dysbiosis plays a role in the development of food addiction. Early-life influences may prime the infant’s gut microbiota and brain for food addiction; this may be further reinforced by increased antibiotic use and dietary habits throughout adulthood. The ubiquity and marketing of cheap, highly palatable, and energy-dense foods may shift this balance toward hedonic eating through both central (perturbations in dopaminergic signaling) and gut-related mechanisms (vagal afferent function, metabolic endotoxemia, changes in gut microbiota). In recent studies, the relationship between food addiction and intestinal microbiota attracts attention. In this context, this review aims to examine the mechanisms between intestinal microbiota and food addiction.